Preservation of Green Environment in Smart Home Project: Formulation of Sustainable Legal Framework - Yeon, Asmah Laili; Basarudin, Noor Ashikin; Mohamed Yusoff, Zuryati; Md Dahlan, Nuarrual Hilal; Mahdzir, Nazli (2017)
Smart home in Malaysia is still new.The installation of smart home gadgets and facilities is on the choice of the home proprietors themselves.There is no specific law and rules which governs the smart home project. The question arise is to what extend the law and policy in Malaysia can accommodate the development of smart home project which gives priority to preserve green environment.Therefore, the objective of the paper is to highlights amendments to the law and policy in ensuring the success of the smart home project and preservation of green environment. This paper is based on a legal doctrinal research and qualitative research. Mixed method was used in analysing the data.Legal doctrinal analysis was performed based on the statutory provisions of housing statutes, codes, and guidelines. Qualitative data were collected by way of interview with 13 experts in the area of smart home and green environment.It is suggested that the Government of Malaysia to recognise the environmental potential of smart features, to commission and support research in establishing a robust evidence base.Some amendments to the existing law and new policy of smart home and green technology should be established to support both agenda.